(3CMcGe GdWGFQI aj Gdabg GdESdGej (B:s (3OQGSI ebGQfI Hjf GdTQjYI hGdbGfhf (B/s - (3GdHQjcj, MSf SGde MSfs ((3HjQhJ ;s (3YeGf, GdCQOf (B:s (3OGQ GdHTGFQ GdESdGejI,s, 2006)
(3SYJ GdOQGSI ddELGHI Ydi GdCSFdI GdJGdjI (B: 1-(3gd jecf COGA GdTYGFQ GdJYHOjI aj GdWGFQI ?(B-2-(3eG Mce QchH GdWGFQI aj GdSaQ ddML ?(B-3-(3gd dSjQ GdWGFQI aj GdLh CKQ Ydi NjGQ GdeLdS ?(B-4-(3eG Mce GdJCejf Ydi GdWGFQI ?(B-5-(3eG gj CMcGe GdVeGf ddCTNGU hGdCTjGA ?(B-6-(3eG gh GdJcjja Gdabgj ddfbd HGdWGFQI ?(B-7-(3eG Mce GdTaYI aj GdWGFQI ? (B8-(3eG Mce GNJWGa GdWGFQGJ ?s
(3GdCUd CWQhMI eGLSJjQ(B-(3LGeYI Ce OQeGf GdESdGejI, (B2005.s
Keywords: (3GdQMdGJ (B((3abg ESdGej(B)s; (3GdYHGOGJ (B((3abg ESdGej(B)s; (3GdeYGedGJ (B((3abg ESdGej(B)s